Gold–alkynyls in catalysis: alkyne activation, gold cumulenes and nuclearity. Issue 32 (14th July 2016) - Halliday, Connor J. V.; Lynam, Jason. M.
Abstract : The use of cationic gold(i ) species in the activation of substrates containing CC bonds has become a valuable tool for synthetic chemists, and the role of metal alkynyls and cumulenes in this chemistry is reviewed. Abstract : The use of cationic gold(i ) species in the activation of substrates containing CC bonds has become a valuable tool for synthetic chemists. Despite the seemingly simple label of 'alkyne activation', numerous patterns of reactivity and product structure are observed in systems employing related substrates and catalysts. The complications of mechanistic determination are compounded as the number of implicated gold(i ) centres involved in catalysis increases and debate about the bonding in proposed intermediates clouds the number and importance of potential reaction pathways. This perspective aims to illustrate some of the principles underpinning gold–alkynyl interactions whilst highlighting some of the contentious areas in the field and offering some insight into other, often ignored, mechanistic possibilities based on recent findings.